Diseño urbano-arquitectónico cultural y recreacional como integrador de zonas fragmentadas en el borde urbano Alpachaca y Azaya - Checa Orbe, Fernanda Elizabeth (2023)
This degree work is developed in the city of Ibarra, in the urban area of Alpachaca and Azaya. The investigation is carried out in an environment that has not been intervened in an architectural and urban way, leaving the parish of Alpachaca with a problem in terms of public space, urban settlement, equipment and security. In order to rehabilitate the urban landscape of the sector while providing a solution to its problems of equipment and connectivity with the downtown areas of the city, an urban-architectural design is proposed in the Latacunga axis connecting the two Alpachaca neighborhoods. and Azaya, through this equipment it is intended to generate various activities so that the urban dynamics change in favor of the use of public space. The project is developed in a user analysis phase and its different activities carried out in public spaces, where the quality of the urban image and the various types of meeting are analyzed, classifying them based on an organization chart, also through surveys will be reached. to the needs of the users, looking for the equipment to solve internal problems such as the lack of cultural spaces and quality public space.